Effects of acrolein in comparison to its prodrug cyclophosphamide on human primary endothelial cells in vitro. (February 2020) - Lau, S.; Rangarajan, R.; Philidet, C.; Krüger-Genge, A.; Braune, S.; Kammerer, S.; Küpper, J.-H.; Lendlein, A.; Jung, F.
Abstract: Cyclophosphamide (CPA) is one of the most successful anticancer prodrugs that becomes effective after biotransformation in the liver resulting in the toxic metabolite acrolein. Cancer is often accompanied by thromboembolic events, which might be a result of dysfunctional endothelial cells due to CPA treatment. Here, the effect of 1 mM CPA or acrolein (10/50/100/500 μM) on human umbilical vein endothelial cells (HUVECs) was analyzed after two days of treatment. The addition of CPA or 10 μM acrolein did not affect HUVECs. However, concentrations of 100 μM and 500 μM acrolein significantly reduced the number of adherent cells by 86 ± 13% and 99 ± 1% and cell viability by 51 ± 29% and 93 ± 8% compared to the control. Moreover, pronounced stress fibers as well as multiple nuclei were observed and von Willebrand factor (vWF) was completely released. Lactate dehydrogenase was 8.5 ± 7.0-fold and 252.9 ± 42.9-fold increased showing a loss of cell membrane integrity. The prostacyclin and thromboxane secretion was significantly increased by the addition of 500 μM acrolein (43.1 ± 17.6-fold and 246.4 ± 106.3-fold) indicating cell activation/pertubation. High doses of acrolein led to HUVEC death and loss of vWF production. This effect might be associated with the increased incidence of thromboembolic events in cancer patients treated with high doses of CPA. Highlights: Acrolein dose-dependently (100 μM and 500 c.f. 0 μM) reduced the number of adherent HUVECs by 86 ± 13% and 99 ± 1%. Acrolein reduced the cell viability by 51 ± 29% and 93 ± 8% compared to the control. Acrolein led to impaired cell membrane integrity, stress fiber formation, and release of von Willebrand factor. Prostacyclin and thromboxane secretion was markedly increased (up to 246-fold) by acrolein, indicating cell perturbation. Acrolein-induced effects might be associated with the increased incidence of thromboembolic events after CPA treatment.